Long Run Association of Oil Prices and Stock Prices: A Case of Indonesia - Muramalla, Venkata Sai Srinivasa Rao; Alqahtani, Hassan Ali (International Journal of Energy Economics and Policy, 2020)
The study was aimed to investigate the long-run association of oil prices with the stock market index of Indonesia. The research consisted of crude oil prices as regressor, stock market index as regressand, GDP growth and inflation as control variables; and for these variables data were collected from 1990 to 2018. Meanwhile, for empirical investigation, ARDL and Granger Causality was applied to identify the long-run and short-run association of the oil crude oil prices with the stock market index in Indonesia. The findings of the study suggest that there is no long-run and short-run association of the crude oil prices with the stock index of Indonesia. However, a bi-directional association between the stock market and GDP growth but at 10%, the empirical study also suggested that GDP growth has unidirectional relation with inflation at 10%; whereas at 5% only stock market granger cause economic growth. Keywords: Stock returns, oil prices, Indonesia JEL Classifications: H54, E31 DOI: https://doi.org/10.32479/ijeep.10241